The Effect of Good Corporate Governance on Tax Avoidance - Julio Sahetapy, Juan; Prasetya, Fernando; Patria Amazia, Naftaly (DINASTI RESEARCH, 2025)
This study seeks to examine the impact of Good Corporate Governance, represented by Institutional Ownership, Board of Commissioners, Audit Committee, and Audit Quality, on tax avoidance in Miscellaneous Industry Manufacturing firms listed on the Indonesia Stock Exchange from 2019 to 2021. This research employs quantitative methodologies utilizing statistical analysis techniques within descriptive models and regression analysis including moderate variables. The sampling method use purposive sampling to select the sample based on certain considerations and criteria aligned with the research objectives. This research aims to furnish policymakers within the organization with insights about the significance of adopting Good Corporate Governance to facilitate Tax Avoidance.